PENGARUH DIGITAL MARKETING DAN KEPERCAYAANTERHADAP KEPUTUSAN PEMBELIAN MELALUI JASA SHOPEE PADA MASYARAKAT DI DESA RAWAN, KECAMATAN KREJENGAN, KABUPATEN PROBOLINGGO - Rifan Antonio Pradana; Lina Budiarti (CV. ADIBA AISHA AMIRA, 2024)
Quantitative research was used in this research study with digital marketing variables (X1), trust (X2), and purchasing decisions (Y). The method for collecting data used was a questionnaire with 60 respondents who were residents of Rawan Village, Krejengan District, Probolinggo Regency using a multistage sampling technique. The information collected in this research was evaluated through the use of multiple linear regression analysis. The partial hypothesis test showed that digital marketing and trust variables had a positive and significant influence on purchasing decisions. And hypothesis testing provides results that digital marketing and trust simultaneously have a positive and significant influence on purchasing decisions. The conclusion from the research that has been researched is that the people of Rawan Village know and are interested in Shopee because they see advertisements on the internet and decide to shop through Shopee because they feel confident in the safety of shopping on the Shopee application